Human rights, state compliance, and social change : assessing national human rights institutions - Goodman, Ryan.; Pegram, Thomas Innes, 1980- (Cambridge : Cambridge University Press, 2012)
'This book critically examines the significance of National Human Rights Institutions by collecting work from experts spanning international law, political science, sociology, and human rights practice'--
Machine generated contents note: 1. National human rights institutions, state compliance, and social change Ryan Goodman and Thomas Pegram; Part I. NHRIs in Theory and Reality: 2. National human rights institutions and state compliance Sonia Cardenas; 3. The shifting boundaries of NHRI definition in the international system Linda C. Reif; 4. Evaluating NHRIs: considering structure, mandate, and impact Julie Mertus; Part II. NHRI Performance: Global, Regional, and National Domains: 5. National human rights institutions and the international human rights system Chris Sidoti; 6. National human rights institutions in anglophone Africa: legalism, popular agency, and the'voices of suffering' Obiora Chinedu Okafor; 7. National human rights institutions in the Asia Pacific region: change agents under conditions of uncertainty Catherine Renshaw and Kieren Fitzpatrick; 8. National human rights institutions in Central and Eastern Europe: the ombudsman as agent of international law Richard Carver; 9. National human rights institutions in Latin America: politics and institutionalization Thomas Pegram; Part III. NHRIS and Compliance: Beyond Enforcement: 10. The societalization of horizontal accountability: rights advocacy and the defensor del pueblo de la naci in Argentina Enrique Peruzzotti; 11. Through pressure or persuasion?: explaining compliance with the resolutions of the Bolivian defensor del pueblo Fredrik Uggla; Part IV. Final Reflections: 12. Tainted origins and uncertain outcomes: evaluating NHRIs Peter Rosenblum; 13. National human rights institutions, opportunities, and activism David S. Meyer.
Includes bibliographical references and index.
Keywords: National human rights institutions; Human rights; International law